2015
DOI: 10.1177/0956462415585668
|View full text |Cite
|
Sign up to set email alerts
|

Lifetime suicide attempt history, quality of life, and objective functioning among HIV/AIDS patients with alcohol and illicit substance use disorders

Abstract: This cross-sectional study evaluated lifetime prevalence of suicide attempts in 170 HIV/AIDS patients with substance use disorders and the impact of suicide attempt history on subjective indices of quality of life and objective indices of cognitive and physical functioning. Compared to their counterparts without a history of a suicide attempt, patients with a history of a suicide attempt (n = 60, 35.3%) had significantly poorer emotional and cognitive quality of life scores (ps < .05), but not physical, social… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
16
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 18 publications
(17 citation statements)
references
References 63 publications
1
16
0
Order By: Relevance
“…The studies were conducted in all the WHO regions: Eighteen studies were conducted in the African Region (11,26,(49)(50)(51)(52)(53)(54)(55)(59)(60)(61)67,71,72,74). Seven studies were conducted in the European Region (4,6,7,13,33,57,65).…”
Section: Participant Characteristicsmentioning
confidence: 99%
See 1 more Smart Citation
“…The studies were conducted in all the WHO regions: Eighteen studies were conducted in the African Region (11,26,(49)(50)(51)(52)(53)(54)(55)(59)(60)(61)67,71,72,74). Seven studies were conducted in the European Region (4,6,7,13,33,57,65).…”
Section: Participant Characteristicsmentioning
confidence: 99%
“…A total of 17 studies conducted in 16 countries (the Argentina, Brazil, China, Estonia, Ethiopia, France, Iran, Indonesia, Korea, Kazakhstan, Nigeria, Tanzania, Taiwan, the United States, South Africa, and Uganda) reported the prevalence of suicide attempts (2,11,31,43,44,46,47,50,52,(55)(56)(57)(58)(59)(60)(61)(62). There were 1035 of 9149 participants in this category, and studies conducted in the region of the Americas countries showed the highest attempted suicide rates (Table 1; Supplemental Digital Content Table S3, http://links.lww.…”
Section: Prevalence Of Suicide Attemptsmentioning
confidence: 99%
“…All 20 studies were cross-sectional. 23 - 42 Twelve were conducted in the United States, 23 - 28 , 30 , 31 , 33 , 37 , 38 , 42 four in Brazil, 32 , 35 , 39 , 41 two in Spain, 36 , 40 one in Argentina, 34 and one in Chile. 29 The age of the participants ranged from 14 to 65 years.…”
Section: Resultsmentioning
confidence: 99%
“…Substance use in PLWH is associated with HIV transmission risk behavior, low antiretroviral therapy (ART) adherence, HIV progression, detectable viral load, and poorer perceived quality of life (Walter & Petry, 2015). Not all substance use that PLWH engage in constitutes an alcohol or substance use disorder; nonetheless, PLWH have reported experiencing physical, social, and psychological harmful effects of substance use.…”
mentioning
confidence: 99%
“…Methamphetamine use also doubles or triples the probability of engaging in high-risk sexual behavior and acquisition of sexually transmitted infections (STIs) including HIV (Colfax & Shoptaw, 2005). HIV infection is more likely in women who use crack cocaine than in women who don’t; suicide attempts for PLWH are more prevalent in persons who use drugs (Walter & Petry, 2015) and are related to poorer emotional and cognitive quality of life measures. Several studies have now demonstrated the relationship between substance use and HIV acquisition and increased morbidity and mortality for PLWH (Kuo et al, 2014).…”
mentioning
confidence: 99%